Sero-monitoring of calf hood vaccination under brucellosis control program in selected states of India during 2016-18 - NAGALINGAM, MOHANDOSS; TRIVENI, KALLESHAMURTHY; SOMY, SKARIAH; KANCHAN, DORNAL; SHOME, BIBEK RANJAN; RAJESWARI, SHOME (The Indian Journal of Animal Sciences, 2022)
The study aimed to evaluate the post-vaccination antibody response in sera of 4-8 months old female calves vaccinated with Brucella S19 vaccine under Brucellosis- Control Program (B-CP) initiated by Department of Animal Husbandry and Dairying (DAH&D), Government of India during 2016-18. The antibody response was extremely good in three states [Telangana (82.53%), Himachal Pradesh (80.97%) and Maharashtra (74.02%)]. Higher antibody response was observed during 21-45 days post-vaccination (DPV) which indicated this period as appropriate for sampling to assess the antibody response. The knowledge acquired with respect to the post-vaccination sero-monitoring in this study will help the ongoing brucellosis control program under the flagship program of Government of India launched in 2019 as National Animal Disease Control Program (NADCP).